2017
DOI: 10.1177/1747493017711949
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian experience in increasing utilization of reperfusion therapies in acute ischemic stroke

Abstract: Background The rate of alteplase (tPA) thrombolysis utilization in acute stroke in Egypt is <1%. We report on the causes of this low rate of reperfusion therapies and take corrective action to improve it. Methods Two prospective observational studies were conducted at Ain Shams University hospitals. The first included 269 acute stroke patients admitted to the hospital over a six-month period. Obstacles to reperfusion therapy were identified, and based on the results, a corrective action plan was implemented in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…Great advancements had occurred in AIS management in Egypt during the last years, but the usage of IV thrombolysis (<1%) is still very far away from the proposed rate [2]. The drug is one of the few evidence-based managements of AIS with the earlier initiation of therapy, the better the clinical response and the lower degree of disabilities [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Great advancements had occurred in AIS management in Egypt during the last years, but the usage of IV thrombolysis (<1%) is still very far away from the proposed rate [2]. The drug is one of the few evidence-based managements of AIS with the earlier initiation of therapy, the better the clinical response and the lower degree of disabilities [10].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrovascular stroke (CVS) is the second most common cause of deaths (after ischemic heart disease) and the third most common cause of disability adjusted life years (after ischemic heart disease and cancer) [1]. The overall crude prevalence rate of stroke in Egypt is 963/100,000 inhabitants [2]. In 1996, the Food and Drug Administration (FDA) had approved IV r-tPA as the only therapy for early acute ischemic stroke (AIS) management and since this date, many efforts have been spent to reduce the stroke onset/needle time owing to the narrow therapeutic window of the drug [3].…”
Section: Introductionmentioning
confidence: 99%
“…Three years ago, since the implementation of the acute stroke protocol in our stroke centers, the rate of revascularization therapy has increased up to about 5 folds. 4 Thus, since the emergence of COVID-19 in Egypt, our main concern was to keep the acute stroke service running with the same efficiency.…”
mentioning
confidence: 99%
“…Over the last 4 years (2016-2020), stroke care in Egypt became in the center of attention of medical health providers. Intravenous recombinant tissue plasminogen activator (r TPA) was endorsed by ministry of health after a study that was conducted to assess the obstacles regarding its availability, and this resulted in 5 times increase in thrombolysis in Ain Shams University stroke centers [3].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Zakaria et al conducted a study in Egypt, to assess the causes of pre-hospital delay that would interfere with early arrival and administration of rTPA, and found that lack of patient or relative awareness about symptoms of stroke and waiting for symptoms to resolve spontaneously, in addition to lacking knowledge about the availability of acute intervention for stroke were the most common causes of prolonged onset to door [ 3 ]. Pre-hospital delay was estimated to range from 3–6 hours, and others reported that only 20% to 25% arrived to emergency within 3 hours of onset [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%